Parasympathetic nervous system dysfunction in primary Sjögren's syndrome. Issue 8 (1st August 2003) - Hočevar, A; Tomšič, M; Praprotnik, S; Hojnik, M; Kveder, T; Rozman, B
Abstract : In the past sicca syndromes were attributed to destruction of glandular tissue. It is now thought that cytokines, autoantibodies, and parasympathetic nervous system dysfunction all have an important role in the xerostomia and xerophthalmia in Sjögren's syndrome.